Barriers and facilitators to palliative care service utilization in Ethiopia: A qualitative systematic review, 2025 - Sadik Abdulwehab; Frezer Kedir (PLoS ONE, 2025)
Introduction Palliative care is a crucial component of end-stage disease management, but its utilization remains low in low- and middle-income countries, such as Ethiopia. This is due to various systemic, social, and policy barriers. Understanding these contextual factors is crucial for developing effective interventions and policy frameworks. This study aimed to explore and synthesize the barriers and facilitators to palliative care service utilization in Ethiopia using a qualitative systematic review approach. Methods This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses of Qualitative Synthesis (PRISMA-Q) guidelines, employing a qualitative systematic design. A comprehensive search was conducted across various databases using tailored keywords and MeSH terms up. The database was searched for every article published on palliative care services up to March 10, 2025, and was updated continuously until it was sent for publication. The data was extracted from March 11–20 and later analyzed from March 21–30, and the report generation till April 10, 2025. Thematic synthesis was used to analyze findings and the Grading of Recommendations Assessment, Development, and Evaluation Confidence in the Evidence from Reviews of Qualitative research approach was employed to assess the confidence of evidence. Results Six studies met the inclusion criteria, encompassing diverse Ethiopian healthcare settings and stakeholders. Five major barriers were identified: policy and governance gaps, health system challenges, knowledge and training deficits, sociocultural and economic constraints, and poor collaboration. In contrast, five facilitators emerged: strong community and family support, intrinsic healthcare provider motivation, integration of palliative care into education, holistic care models, and stakeholder engagement. High confidence was assigned to four themes, underscoring their significance and applicability. Conclusion The underutilization of palliative care in Ethiopia stems from intertwined structural, educational, and sociocultural challenges. However, promising facilitators exist that can guide policy reform and intervention design. Addressing these barriers through improved policies, workforce development, and community engagement is imperative for ensuring equitable access to quality palliative care services.